2009
DOI: 10.1088/0004-637x/702/1/368
|View full text |Cite
|
Sign up to set email alerts
|

Sharpening the Precision of the Sunyaev-Zel'dovich Power Spectrum

Abstract: Using both halo model calculations and a large sample of simulated SZ maps, we demonstrate that high-mass clusters add significant non-Gaussian variance to measurements of the SZ power spectrum amplitude. The difficulty in correctly accounting theoretically for the contribution of these objects to the uncertainty in C leads to a reduced sensitivity to σ 8 . We show that a simple solution is to mask out the brightest clusters in the map before measuring the power spectrum. We demonstrate that fairly conservativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 51 publications
(82 reference statements)
4
67
0
Order By: Relevance
“…the most non-Gaussian features) from the power spectrum improves the errors on Ω m and σ 8 , the errors being smallest for an optimal threshold ν th,opt ≈ 6. Although the counter-intuitive increase in the performance that we observe when discarding the resolved part of the data is not so surprising, since the impact of non-Gaussianities on the power spectrum is lowered (Shaw et al 2009 observe a similar trend for Sunyaev-Zel'dovich clusters), we should note here that it could be exacerbated if our analysis is close to the Fisher matrices formalism's limits. Moreover, there may be an optimal weighting scheme that would both allow for the signal in the resolved part and minimize its non-Gaussian errors.…”
Section: Resultsmentioning
confidence: 52%
“…the most non-Gaussian features) from the power spectrum improves the errors on Ω m and σ 8 , the errors being smallest for an optimal threshold ν th,opt ≈ 6. Although the counter-intuitive increase in the performance that we observe when discarding the resolved part of the data is not so surprising, since the impact of non-Gaussianities on the power spectrum is lowered (Shaw et al 2009 observe a similar trend for Sunyaev-Zel'dovich clusters), we should note here that it could be exacerbated if our analysis is close to the Fisher matrices formalism's limits. Moreover, there may be an optimal weighting scheme that would both allow for the signal in the resolved part and minimize its non-Gaussian errors.…”
Section: Resultsmentioning
confidence: 52%
“…As the predictions for the SZ power spectrum available today (see, e.g., Shaw et al 2009;Sehgal et al 2010, and references therein) are similar to the prediction of Komatsu & Seljak (2002) (for example, Lueker et al 2010 found A SZ = 0.55 ± 0.21 for the prediction of Sehgal et al 2010, which is based on the gas model of Bode et al 2009), a plausible explanation for a lowerthan-expected A SZ is a lower-than-expected gas pressure. Arnaud et al (2007) find that the X-ray observed integrated pressure enclosed within r 500 , Y X ≡ M gas,500 T X , for a given M 500 is about a factor of 0.75 times the prediction from the Cooling+SF simulation of Nagai et al (2007).…”
Section: Discussionmentioning
confidence: 68%
“…By combining SPT survey maps at 150 and 220 GHz to minimize astrophysical foreground signals, Lueker et al (2010) were able to isolate and detect SZ power (kinetic plus thermal) at 2.6σ . The measured amplitude at = 3000 was 4.2 ± 1.5 μK 2 , significantly below that predicted by halo model calculations (Komatsu & Seljak 2002) or simulations (White et al 2002;Shaw et al 2009;Sehgal et al 2010), assuming WMAP7 cosmological parameters. The significantly lower-than-predicted signal could be explained by a lower value of σ 8 .…”
Section: Introductionmentioning
confidence: 58%